Volume 3: Design and Analysis 2008
DOI: 10.1115/pvp2008-61177
|View full text |Cite
|
Sign up to set email alerts
|

FEM Stress Analysis of Tee Intersections With LTA

Abstract: In this work a three-dimensional finite element study is carried out of pressurized piping tee (tee) intersections, with local area wall thinning (LTA). Two types of stress analysis are carried out, dealing respectively with the determination of the stress concentration factor (SCF), and of the plastic collapse load. Stress values determined for vessels with uniform thickness are compared with previously published work. An evaluation is then made of the effect on the SCF values of varying the size and shape of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was found that the total stress value under the combined loads was not completely equal to the total value gotten by adding the two stress states under separate loads. Ahmad et al [179] carried out a 3D FE study on stress analysis in pressurized piping tee intersections. Then the stress concentration factor and the plastic collapse load were found for intersections with different depths of wall thinning.…”
Section: Cylinder-cylinder Intersectionsmentioning
confidence: 99%
“…It was found that the total stress value under the combined loads was not completely equal to the total value gotten by adding the two stress states under separate loads. Ahmad et al [179] carried out a 3D FE study on stress analysis in pressurized piping tee intersections. Then the stress concentration factor and the plastic collapse load were found for intersections with different depths of wall thinning.…”
Section: Cylinder-cylinder Intersectionsmentioning
confidence: 99%